Literature Review: Perbedaan Pemberian Oksitosin Profilaksis Secara Intravena dan Intramuskular Terhadap Kejadian Perdarahan Postpartum - Cahyaningtyas, Dwi Kartika; Rospia, Evi Diliana; Agustina, Rika (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Postpartum Haemorrhage is a condition of blood loss of more than 500 cc that occurs within 24 hours after delivery. Postpartum hemorrhage is a significant cause of morbidity and mortality in childbirth. Postpartum Haemorrhage occurs in about 1% to 6% of all deliveries. Uterine atony, the leading cause of primary postpartum hemorrhage, accounts for 70% to 80% of all bleeding. Early prevention in postpartum hemorrhage cases is the usage of uterotonics in the third stage of labor which has become the standard of intervention worldwide. The choice of uterotonic in managing postpartum hemorrhage should be adjusted to the administration and dosage. This Study aims to analyze the difference in prophylactic administration of oxytocin injected in intramuscular and intravenous during postpartum hemorrhage. Data were searched using PICO, articles were selected using PRISMA, and critical appraisal. There is decreased postpartum hemorrhage compared to IM oxytocin administration. Intra Vena oxytocin administration could reduce the incidence of severe postpartum hemorrhage and prevent blood transfusions compared to IM oxytocin administration in the third stage of labor in postpartum hemorrhage. However, there was no significant difference in hemoglobin changes. The side effects caused by intravenous administration are still manageable compared to intramuscular administration. Intravenous oxytocin prevented postpartum hemorrhage in stage III more effectively than intramuscular administration. The side effects that emerged in the two groups of intravenous and intramuscular administration were not significantly different and were still within mild limits. The administration of oxytocin in preventing postpartum hemorrhage in the third stage of labor has become a procedure and recommendation of health organizations.